IMPLEMENTATION OF VLOG MEDIA IN GROWING RELIGIOUS CHARACTER IN EARLY CHILDREN IN THE ERA SOCIETY 5.0 - Iltiqoiyah, Lutfiatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out vlog media in developing religious character in early childhood in the era of society 5.0. which was carried out at the Raudlatul Athfal Al-Iman Kraksaan institution, Probolinggo, using qualitative methods of case study types. The informants in the study were the principal and the teacher council. The results of this study show that in the process of learning religious character in early childhood based on Vlog media as follows: first, analyze the needs of Vlog media in religious character education in early childhood. Second, create the right learning design by using Vlog media. Third, create Vlog content that contains religious character values. Fourth, publish Vlogs so that they are easily accessible. Fifth, conduct an evaluation.